Carotenoids from Cyanobacteria: A Biotechnological Approach for the Topical Treatment of Psoriasis - Graciliana Lopes; Duarte Clarinha; Vitor Vasconcelos (Microorganisms, 2020)
In this study, five cyanobacteria strains (Alkalinema aff. pantanalense LEGE15481, Cyanobium gracile LEGE12431, Nodosilinea (Leptolyngbya) antarctica LEGE13457, Cuspidothrix issatschenkoi LEGE03282 and Leptolyngbya-like sp. LEGE13412) from the Blue Biotechnology and Ecotoxicology Culture Collection (LEGE CC) of CIIMAR were explored for their biotechnological potential in the treatment of psoriasis. Different extracts were characterized for their pigment profile by HPLC-PDA. The antioxidant potential of the extracts was assessed against the superoxide anion radical (O2•-). Their anti-inflammatory and antiproliferative potential was assessed in vitro using the macrophages RAW 264.7 and the human keratinocytes HaCaT as cell-line models, respectively. Terrestrial and freshwater strains presented the highest carotenoid content (33193−63926 μg/g dry extract), with all-trans-β-carotene, zeaxanthin, echinenone and lutein derivatives being the most abundant carotenoids. Acetone was the most effective solvent for pigment extraction. The acetone extracts presented the lowest IC50 values (0.29−0.38 mg dry extract/mL) regarding O2•- scavenging, and revealed anti-inflammatory potential, with N. antarctica LEGE13457, A. pantanalense LEGE15481 and Leptolyngbya-like sp. LEGE13412 reducing the nitric oxide (NO) in RAW 264.7 cell culture medium in about 25% (p < 0.05). With the exception of A. pantanalense LEGE15481, all the extracts significantly reduced keratinocyte proliferation (p < 0.05), demonstrating a selective toxicity among the different cell lines. Overall, Leptolyngbya-like sp. LEGE13412 and N. antarctica LEGE13457 seem promising for further exploitation in the framework of psoriasis, due to their antioxidant, anti-inflammatory and antiproliferative potential.